Intention to purchase halal certified product among non-muslim customers: a case of Iban students of high institution in Kota Samarahan / Eliofina Minni Burthon - Burthon, Eliofina Minni (2018)
Halal product in the market not only consumes by Muslim consumers, but it also have demand from non-Muslim consumers as well. This research paper is aim to investigate the factors of attitude, subjective norm, halal awareness and halal certification toward intention to purchase halal certifiedproduct among Iban students ofhigh institution in Kota Samarahan. Total of150 questionnaires were distribute to the Iban students at UiTM and UNIMAS, Sarawak. The self- administered questionnaire was distributed to the respondents in order to collect the data and information. The result of this research show that halal certification is the most factor that influence the intention to purchase halal certified product among Iban students of high institution in Kota Samarahan.